Sisterhood in Question: Rewriting a Life of Binaries in Margaret Atwood’s The Penelopiad - Zubair Baig, Mirza Muhammad (Journal of Research in Humanities, 2023)
In Atwood’s The Penelopiad (2005), a feminist rewrite of Penelope’s character from Homer’s Odyssey, we find that a relationship among women as shown in the novella is dysfunctional and fractured. The subject position of a woman in the narrative has not been of great help to objectified women to the disadvantage of women and their rights. The narrative voice of a woman has not addressed the patriarchal and ideological world constructed on the binaries among women. The women, even in Atwood’s writing, have been portrayed in the stereotypical fashion which disrupts sisterhood among female characters and exhibits differential power relations among them. Instead of writing back to the patriarchal canon, we read in the text about the Penelope-Helen rivalry, Penelope-Actoris mistress-slave relationship, EurycleiaAnticleia tug of war and their displacing Penelope as Odysseus’s deputy in the house in his absence, and Penelope’s narrative and maids’ counter-narrative reflecting on how their uneven relationship capitalized on maids’ horrendous slavish sufferings.